2019
DOI: 10.3389/fpsyg.2019.00691
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control as a 5-HT1A-Based Domain That Is Disrupted in Major Depressive Disorder

Abstract: Heterogeneity within Major Depressive Disorder (MDD) has hampered identification of biological markers (e.g., intermediate phenotypes, IPs) that might increase risk for the disorder or reflect closer links to the genes underlying the disease process. The newer characterizations of dimensions of MDD within Research Domain Criteria (RDoC) domains may align well with the goal of defining IPs. We compare a sample of 25 individuals with MDD compared to 29 age and education matched controls in multimodal assessment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 147 publications
(218 reference statements)
0
8
0
Order By: Relevance
“…Preliminary data and published studies include targeted seed-based analyses of connectivity between PCC (DMN node) and left inferior temporal gyrus (CCN node) [ 46 , 47 , 58 , 60 , 62 , 64 69 ]. Connectivity of PCC to inferior frontal gyrus (also CCN) was considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data and published studies include targeted seed-based analyses of connectivity between PCC (DMN node) and left inferior temporal gyrus (CCN node) [ 46 , 47 , 58 , 60 , 62 , 64 69 ]. Connectivity of PCC to inferior frontal gyrus (also CCN) was considered.…”
Section: Methodsmentioning
confidence: 99%
“…The CCN is a distinct network of distributed neural nodes that broadly supports integrative executive functions such as inhibitory control, working memory, and sustained complex attention [ 59 ]. One function of inhibitory control is its ability to modulate negative affective processes, including rumination [ 46 , 60 , 61 ]. Consistent with a CCN disruption hypothesis of elevated rumination, rs-fMRI studies have reported that disrupted/elevated DMN-CCN connectivity (and decreased within CCN connectivity) is associated with increased rumination and decreased inhibitory control [ 46 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the neural, cognitive, information processing, and psychological patterns discussed above have broad transdiagnostic relevance, particularly with respect to other disorders of negative affect (e.g., anxiety, trauma-related conditions) 140 -that likewise respond to pharmacologic interventions with plasticity-enhancing properties 141,142 . Equally noteworthy, however, is the marked heterogeneity of depressed patients, which is evident at the neural network 143,144 , cognitive 145 , information processing 145,146 , and clinical 147 levels, and may help to explain the fact that no known intervention strategy is effective for all depressed patients. Rather than assuming a unitary etiology, and a correspondingly uniform pathway to recovery from depression, a focus on establishing correlations across levels of analysis-both before and after administering plasticity-enhancing interventions-will help to clarify the degree to which an integrative neuroplasticity model may be relevant to some individual forms of depression and negative affect, but not others 140 .…”
Section: Generalizability and Transdiagnostic Relevancementioning
confidence: 99%
“…Furthermore, tryptamines involve more 5-HT 1a R agonism than phenethylamines ( Halberstadt and Geyer, 2011 ). The 5-HT 1a R has been shown to play a role in cognitive control in both humans ( Langenecker et al, 2019 ) and animals ( Baba et al, 2015 ). In addition, use of a 5-HT 1a agonist over the course of 6 weeks has been shown to increase executive functioning in patients with schizophrenia ( Sumiyoshi et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%